In vivo gene transfer methods into bladder without viral vectors - Sugimura, K (Hinyokika kiyo. Acta urologica Japonica, 1997)
For the application of gene therapy to bladder cancer, we examined four in vivo gene transfer methods without viral vectors. For lipofection cationic liposomes (Lipofectin) were instilled into murine bladders. The hemagglutinating virus of Japan (HVJ)-liposomes possessing membrane fusion activity were also injected intraluminally. Using a particle gun, rabbit bladder mucosa was bombarded with DNA-coated gold microcarriers. Electrotransfection was examined in rabbit bladder by pulse direct currents (0.15-0.2 A, 50 msec, repeated 8 times) generated between needle electrodes after submucous injection of DNA solution. beta-galactosidase gene and chloramphenicol acetyltransferase (CAT) gene were used as marker genes. Although lipofection was inefficient in normal urothelium, cancerous urothelium was transfected slightly. HVJ-liposomes more efficiently transfected superficial layers of urothelium with a peak of expression on day 5. The particle gun produced non-uniform but efficient transfection in deeper layers of the urothelium. By electrotransfection, submucous interstitial cells were transfected as well as urothelium. No major complications were observed after these four procedures. HVJ-liposomes are potentially useful for the treatment of carcinoma in situ and the latter two methods may be suitable for the adjuvant therapy of localized bladder tumors